Leber congenital amaurosis caused by Lebercilin (LCA5) mutation: Retained photoreceptors adjacent to retinal disorganization - Jacobson, Samuel G. (Molecular Vision, 2009)
PURPOSE: To determine the retinal disease expression in the rare form of Leber congenital amaurosis (LCA) caused by Lebercilin (LCA5) mutation. METHODS: Two young unrelated LCA patients, ages six years (P1) and 25 years (P2) at last visit, both with the same homozygous mutation in the LCA5 gene, were evaluated clinically and with noninvasive studies. En face imaging was performed with near-infrared (NIR) reflectance and autofluorescence (AF); cross-sectional retinal images were obtained with optical coherence tomography (OCT). Dark-adapted thresholds were measured in the older patient; and the transient pupillary light reflex was recorded and quantified in both patients. RESULTS: Both LCA5 patients had light perception vision only, hyperopia, and nystagmus. P1 showed a prominent central island of retinal pigment epithelium (RPE) surrounded by alternating elliptical-appearing areas of decreased and increased pigmentation. Retinal laminar architecture at and near the fovea was abnormal in both patients. Foveal outer nuclear layer (ONL) was present in P1 and P2 but to different degrees. With increasing eccentricity, there was retinal laminar disorganization. Regions of pericentral and midperipheral retina in P1, but not P2, could retain measurable ONL and less laminopathy. P2 had a small central island of perception with >5 log units of sensitivity loss. Pupillary responsiveness was present in both LCA5 patients; the thresholds were abnormally elevated by ≥5.5 log units. CONCLUSIONS: LCA5 patients had evidence of retained photoreceptors mainly in the central retina. Retinal remodeling was present in pericentral regions in both patients. The NIR reflectance and NIR-AF imaging in the younger patient suggested preserved RPE in retinal regions with retained photoreceptors. Detailed phenotype studies in other LCA5 patients with longitudinal follow-up will help determine the feasibility of future intervention in this rare disease.